ESTIMATION OF THE FIRST MATURITY SIZE OF SILVER BARB (Barbonymus gonionotus) IN SIDENRENG LAKE, SOUTH SULAWESI - Hasrianti Hasrianti; Gondo Puspito; Budhi Hascaryo Iskandar; Mohammad Imron; Wazir Mawardi (Jurnal Teknologi Perikanan dan Kelautan)
Silver barb is a popular introduced species in Sidenreng Lake, South Sulawesi. Its presence has been highly beneficial for local fishers due to its significant economic value. Fishers make this fish their primary target for fishing. The fishing activity for the silver barb was carried out year-round using gill nets with various mesh sizes, ranging from small to large (1.5”, 2”, 2.5”, 3”, and 3.5”). These activities have led to a decline in the fish population in the Lake. Therefore, information related to the fisheries biology of the fish is crucial. This study aims to determine the length at first capture (Lc), length at first maturity (Lm), and the appropriate gill net mesh size for catching suitable silver barb. The sample data were analyzed using descriptive and comparative statistical tests. The study results showed that the size at capture for the silver barb in the Sidenreng Lake was Lc = 132.66 mm. Male and female fish reach their first length of maturity at fork lengths (FL) of 173.08 mm and 140.95 mm, respectively. The recommended gill net mesh size for catching suitable silver barb was 3”, as the average FL caught was larger than the Lm value.